2015
DOI: 10.1016/j.freeradbiomed.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mechanics and metabolic dysfunction

Abstract: Desmosplasia is a characteristic of most solid tumors and leads to fibrosis through abnormal extracellular matrix (ECM) deposition, remodeling and post translational modifications. The resulting stiff tumor stroma not only compromises vascular integrity to induce hypoxia and impede drug delivery, but also promotes aggressiveness by potentiating the activity of key growth, invasion, and survival pathways. Intriguingly, many of the pro-tumorigenic signaling pathways which are mechanically activated by ECM stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 154 publications
(194 reference statements)
6
75
0
Order By: Relevance
“…Here, the identification of glutaminolysis as a mechanoactivated process coregulated with aerobic glycolysis advances our understanding of the regulatory hierarchy seen in the metabolic reprogramming in PH. Such an interface between stiffness and metabolism draws parallels to related reprogramming events proposed in tumors in relation to matrix remodeling (29). By its direct causative relation to metabolic dysregulation, it also reinforces the paradigm of vascular stiffness as an initiating pathogenic trigger of this disease rather than merely an end-stage feature.…”
Section: The Yap/taz-gls Axis Induces Glycolysis and Glutaminolysis Isupporting
confidence: 54%
“…Here, the identification of glutaminolysis as a mechanoactivated process coregulated with aerobic glycolysis advances our understanding of the regulatory hierarchy seen in the metabolic reprogramming in PH. Such an interface between stiffness and metabolism draws parallels to related reprogramming events proposed in tumors in relation to matrix remodeling (29). By its direct causative relation to metabolic dysregulation, it also reinforces the paradigm of vascular stiffness as an initiating pathogenic trigger of this disease rather than merely an end-stage feature.…”
Section: The Yap/taz-gls Axis Induces Glycolysis and Glutaminolysis Isupporting
confidence: 54%
“…Alternatively, when the TKIs do not exert vascular normalization or cause excessive vascular pruning, TKI treatment would add no benefit to chemotherapy. In a preclinical study, we demonstrated that measuring tumor hypoxia with 18 F-fluoromisonidazole PET mirrored the status of vascular normalization. We incorporated this technique in the neoadjuvant setting of breast cancer patients treated with the TKI nintedanib in combination with chemotherapy.…”
Section: Translational Relevancementioning
confidence: 98%
“…We hypothesized that tracing the tumor stromal oxygenation levels with 18 F-fluoromisonidazole-positron emission tomography (18F-FMISO-PET) during a WoO would allow detecting the patients that are or are not candidates for nintedanib therapy. The justification of this hypothesis is that it is widely accepted that abnormal stroma is hypoxic as well (5,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clearly evident that tumors contain various non-cancer cells including fibroblasts, vascular endothelial cells, immune cells -with T-cells as potent mediators of antitumor immunity -and soluble factors [2][3][4] that, in dynamic reciprocity with cancer cells, make up the tumor microenvironment (TME). TME is organ-specific in terms of interstitial cells and extracellular matrix (ECM), which condition tissue oxygen levels and pH, adding further layers of complexity [5,6].…”
Section: Introductionmentioning
confidence: 99%